Compensation projects priority assessment by various population groups in the Arctic industrial development - E. V. Potravnaya; O. A. Krivoshapkina (Вестник университета)
The article is devoted to the issues of taking into account of the population’s opinion in the implementation of the Arctic industrial development projects. Evaluation methods and selection procedures for compensation projects have been proposed, as well as their ranking is made. On the example of a project for the placer diamonds extraction at the Molodo River deposit in the Bulunsky district of the Sakha Republic (Yakutia), and based sociological surveys of the population, projects aimed at preserving the ancestral habitat of indigenous small-numbered peoples of the North, supporting traditional crafts, building infrastructure facilities taking into account the individual groups opinions of the population, are proposed. The article is based on the materials of the ethnological expertise of this project and the results of the authors’sociological research. The proposals for the selection of compensation projects for the local population in the conditions of evaluation criteria plurality are formulated.